Going back home: Internal return migration in rural Tanzania - Hirvonen, Kalle; Lilleør, Helene Bie (Elsevier, 2015)
While reasons for out-migration are relatively well understood, little is known about why people return to their rural origins. We contribute to filling this gap in the literature by using 19-year tracking data from rural Tanzania to estimate the patterns and determinants of return migration, and we find that return is largely associated with unsuccessful migration. For men, return is linked to poor job-market outcomes at the migration destination, and for women, to the ending of marriages. Female migrants who exchange transfers with relatives at home, and men who are financially supported by their families, are more likely to return.